Tinjauan Yuridis terhadap Penyelesaian Sengketa Merek Internasional antara Industri Berbeda - Tasya Darosyifa; Ligina Tesalonika; Ariel Lois; Angel Evelyn; Aditama Candra Kusuma; Irwan Triadi; Iwan Erar Joesoef (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
International trademark infringement poses a complex challenge for brand owners due to jurisdictional variations and differing legal systems across countries. This study examines available legal remedies, ranging from non-litigation dispute resolution mechanisms such as Alternative Dispute Resolution (ADR) - encompassing negotiation, mediation, and arbitration - to formal litigation in national courts. ADR offers advantages in time efficiency, cost-effectiveness, and confidentiality, while litigation provides legal certainty through binding court decisions such as injunctions and damages awards. Preventive strategies including international trademark registration through the Madrid System and cooperation with customs authorities serve as crucial proactive protection measures. Furthermore, this research analyzes judicial considerations in cross-industry trademark disputes, including assessment of trademark similarity (visual, phonetic, conceptual), reputation of well-known marks, bad faith of infringers, and potential consumer confusion. Case studies such as Louis Vuitton vs. Louis Vuitton Dak and Zara Food vs. Zara Fashion demonstrate judicial application of the likelihood of confusion principle and anti-dilution doctrine even across different industries. The research employs normative legal methodology with statutory and secondary document analysis approaches. Findings confirm that legal strategy selection must consider infringement scale, jurisdiction, and business objectives, while international trademark protection requires integration of proactive registration, legal enforcement, and comprehensive understanding of global market dynamics.